Reliability of the Infraspinatus Test in Carpal Tunnel Syndrome: A Clinical Study - Marek A. Meder (Journal of Clinical and Diagnostic Research, 2017)
Introduction: Recently, a standardized provocation tests for the infraspinatus muscle, the Infraspinatus test (IsT), aimed at clinically confirming Carpal Tunnel Syndrome (CTS), was validated in a multiple-blind, controlled study. Aim: The present study was conducted to investigate interrater reliability of the IsT under conditions as they occur in daily clinical practice, since this is essential for acceptance of any new test. Materials and Methods: Two raters from different medical disciplines used the IsT in the same group of subjects at different localities and with an interval of two to four weeks. Arms with symptoms of CTS were examined and compared with a control group of arms without symptoms. Nerve conduction studies were performed in all the subjects. Statistical analysis was performed with Cohen's Kappa (for inter-rater reliability) and McNemar's test (for determining dependencies between arms and raters). Results: A total of 34 subjects (age 35-86 years) were investigated with the IsT by two raters in a blinded fashion. There was a high agreement between raters with a Kappa statistic of κ=0.868, when performing this new provocation test. The McNemar test did not reveal dependencies between Rater A and Rater B (p=0.6171), nor between the left and right arms of subjects (Rater A: p=0.4533, Rater B: p=0.5023). Conclusion: The new provocation test of the infraspinatus muscle is not only capable of confirming CTS, as was shown before, but is also a reliable method for use by different examiners under customary conditions.